Displacement Of Migrant Workers In Malaysia - Rahim, Rohani Abdul; Bakar, Kamarudin Abu; Tajuddin, Muhammad Afiq Ahmad (Universiti Sains Malaysia, 2016)
Paradoxically, while the demand for foreign workers in Malaysia is increasing due to mega developments, the possibility of social protection for migrant workers has been restricted. The need for decent accommodation, health care, are not in State agenda. Refusing to accept social protection responsibility tend to displace migrant workers. This kind of displacement of migrant workers are incompatible with goals of creating conditions of equity and social protection as enshrined in the Federal Constitution on fundamental liberty. This is due to development planning that are more interested on macro-scale gain but refusing to assume responsibility when migrant workers become displace upon relocation and replacement for work. Migrant workers who are regulated to work in Malaysia are not regulated by a special social protection regime but by employment agents and outsourcers who are keen of profiteering rather than ensuring their wellbeing while in the placement process. Similarly, the enforcers are more keen to legalize workers or deporting them accordingly while displace migrant workers needs support to be able to find job since they have been a while in the receiving country. This paper intends to dwell into the reasons for the displacement of migrant workers in Malaysia. The fact that they were in the country, there is possibility to regularize the migrant workers to become documented worker, and being a receiving country it is a duty to provide social protection for these migrant workers until the document expired. For this reason, Malaysia should deal with displaced migrant workers differently from other kind of migration offences because in the long run Malaysia would be able to benefit from these displaced migrant workers in the midst of Malaysia becoming developed country in the near future. The ability to manage displaced migrant workers will benefit all parties, that are the sending countries (receiving continual remittance), the receiving country (influx of labour sources) and the workers themselves (continual productive to produce products). On the other hand, failing to manage migrant workers accordingly may lead to violation of the human rights principles and may depreciate Malaysia image globally.